2016
DOI: 10.1007/s00266-016-0658-1
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Management of Intravascular Injection with Facial Fillers: Results of a Multinational Survey of Experienced Injectors

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 18 publications
0
59
0
1
Order By: Relevance
“…The results of an internet-based survey conducted on 52 experienced injectors worldwide showed that a 62% of them reported one or more intravascular injections [ 32 ]. Recognition of a vascular event and swift and aggressive treatment is necessary to avoid potentially irreversible complications [ 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of an internet-based survey conducted on 52 experienced injectors worldwide showed that a 62% of them reported one or more intravascular injections [ 32 ]. Recognition of a vascular event and swift and aggressive treatment is necessary to avoid potentially irreversible complications [ 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…106,125 Time is short for the physician to intervene; prompt recognition of the problem, particularly appearance of pain, skin discoloration allows treatment to be stopped and complication treatment started immediately; topical nitropaste under occlusive dressing, high dose of hyaluronidase, oral acetylsalicylic acid (aspirin), warm compresses and vigorous massage have been recommended; secondary lines of treatment may involve hyperbaric oxygen therapy and ancillary vasodilating agents such as prostaglandin E1. [126][127][128] A metanalysis of vascular complications of facial fillers provides an interesting update. 129 To conclude, complications caused by dermal fillers are rare and mostly minor and injection-related but physicians have to be aware of the risk and be able to manage and treat adverse events, particularly the severe ones.…”
Section: Treatment Guidelines For Pcl Filler Complicationsmentioning
confidence: 99%
“… 38 However, even expert esthetic physicians have a substantial history of intravascular injection in their careers with 61% of trainers inducing at least one such episode. 39 …”
Section: Applied Facial Anatomymentioning
confidence: 99%